The influence of experience on kinetic characteristics of the looped longswing - Williams, G.; Irwin, G.; Kerwin, D. G.; Newell, K. M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to increase understanding of the strategies performers use to complete the looped longswing (LLS) in order to provide useful information for the development of this skill. For an elite gymnast and two novice performers, kinematic and kinetic data were collected during 5 series of three LLS (CODA motion analysis system, 200 Hz; instrumented high bar, 1 kHz). Inverse dynamics were employed to determine joint kinetics during the second LLS in each trial for each performer. The elite gymnast performed positive work at the hips during the ownswing resulting in hip flexion, which facilitated the control of proceeding functional phase actions. Peak shoulder power values were highest for the elite gymnast and lowest for the least experienced novice participant.